Pengaruh Kerja Sama Tim, Komunikasi dan Disiplin Kerja Terhadap Kinerja Karyawan di CV Multi Agro Sarana Sumedang - Nuraini, Risda; Sudaryo, Yoyo (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
Performance is the attempt made by a worker to fulfill a duty assigned by the organization. Performance is a critical factor in determining a company's success since, without it, the business will struggle to meet its goals. This study investigates how work discipline, cooperation, and communication affect output. 56 workers from a single company in Sumedang City, West Java, Indonesia, made up the sample. Respondents are given questionnaires as part of a quantitative approach. Tests for validity and reliability were used to evaluate the study instrument. The analysis technique used is multiple linear regression. The study's results demonstrated that discipline, teamwork, and communication all significantly and favorably affect worker performance